2019
DOI: 10.1111/dom.13683
|View full text |Cite
|
Sign up to set email alerts
|

Delays in anti‐hyperglycaemic therapy initiation and intensification are associated with cardiovascular events, hospitalizations for heart failure and all‐cause mortality

Abstract: Aims The aims of this study were to assess the impact of delays in treatment intensification (TI) on cardiovascular events, heart failure, and all‐cause mortality at typical stages of anti‐hyperglycaemic therapy. Materials and Methods Using electronic health record data, we created three TI cohorts of diabetes patients who: 1) initiated metformin (MET) as their first anti‐hyperglycaemic therapy; 2) added a sulfonylurea (SU) to MET; and 3) initiated insulin (INS) while using MET or SU, alone or in combination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Therefore, longer exposure of the cells to the hyperglycaemic condition caused increased in oxidative stress thus more difficult in treating the hyperglycaemic conditions (31). Prolonged hyperglycaemia is also known to affect the prognosis and outcome of patients as delay in the intensification of treatment might increase risk in developing cardiac event that could lead to fatality (32). In this study, metformin treatment also showed no significant reduction in blood glucose.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, longer exposure of the cells to the hyperglycaemic condition caused increased in oxidative stress thus more difficult in treating the hyperglycaemic conditions (31). Prolonged hyperglycaemia is also known to affect the prognosis and outcome of patients as delay in the intensification of treatment might increase risk in developing cardiac event that could lead to fatality (32). In this study, metformin treatment also showed no significant reduction in blood glucose.…”
Section: Discussionmentioning
confidence: 52%
“…The protective effect of metformin seems to be influenced by the rapidity of therapy initiation, the persistence with treatment, and distinct patient characteristics. An analysis of electronic health records of the Kaiser Permanente Northwest and Mid‐Atlantic States regions demonstrated that a delayed initiation of metformin therapy in drug‐naïve patients was associated with a significantly increased risk of hospitalization for heart failure and all‐cause mortality 40 . A recent Italian case–control study evaluated the protective effect of oral hypoglycaemic agents in a large cohort of elderly T2D subjects, 67% of whom were on metformin treatment 41 .…”
Section: Efficacy On Mortality and Cardiovascular Outcomesmentioning
confidence: 99%
“…An analysis of electronic health records of the Kaiser Permanente Northwest and Mid-Atlantic States regions demonstrated that a delayed initiation of metformin therapy in drug-naïve patients was associated with a significantly increased risk of hospitalization for heart failure and all-cause mortality. 40 A recent Italian case-control study evaluated the protective effect of oral hypoglycaemic agents in a large cohort of elderly T2D subjects, 67% of whom were on metformin treatment. 41 The study concluded that, with the exception of very elderly patients (aged >85 years), increased adherence to metformin therapy was associated with reduced risk of mortality.…”
Section: Efficacy On Mortality and Cardiovascular Outcomesmentioning
confidence: 99%
“…When facing elevated HbA1c levels, patients are often daunted by factors such as their own or their provider's reluctance to change (‘therapeutic inertia’), regimen complexity or cost. There are often long 2 and detrimental 3 delays in initiating or intensifying insulin as a result.…”
Section: Introductionmentioning
confidence: 99%